Improving Students Performance in Fluid Mechanics Course through Remedial Action - Abreham Bekele Bayu (EDUCATIO : Journal of Education, 2020)
This research study aims to improve students’ performance in the Fluid mechanics course through active learning methods. The method for this research was conducted on a longitudinal study design. It takes about four-month interventions in teaching the course by using active learning methodologies following with tutorials. The study population number and the target groups were also identified by the guidance and support given by the Jimma University Institute of Technology registrar. Before handling the research, all the essential conditions were done such as giving orientation, fixing the duration of the study, and rearrangement of the program according to the interest of most of the students. The sampling technique used was availability sampling. The sample size was included for year II both female and male students of Fluid mechanics course students in the second semester of 2019. After this secondary data was collected from the Jimma University Institute of Technology registrar office and questionnaires collected from the second-year students; reached with the problem of the nature of the course. Therefore, we conclude that the study output indicates that the percentage of passed students increased from 66.92% to 91.82% after active learning methodology training had given for instructors in addition to delivering on spot tutorial. The group study recommends that active leaning methodology can improve the performance of the students and the school should have to emphasize this methodology in addition to monitoring and appreciating on spot tutorial.